Tectonic and environmental controls on palaeozoic fluvial environments: Reassessing the impacts of early land plants on sedimentation - Santos, Maurício G. M. [UNESP]; Mountney, Nigel P.; Peakall, Jeff (Geological Society of London, 2017)
The apparent increase in occurrence of meandering fluvial channel systems in the Middle Palaeozoic has long been related to the effects of land-plant colonization. However, evidence for meandering channels in non-vegetated settings is shown by pre-vegetation successions on Earth, from the prevalence of meandering channels on Mars, from physical modelling of meandering channels, and from non-vegetated channels in modern desert basins. In addition, early land plants had small dimensions, were limited in their occurrence, and were dependent on environmental factors. Here, we question the capacity of early land plants to impose the major impacts suggested by current models.We propose that the sudden widespread occurrence on Earth of fluvial deposits indicative of the accumulation of meandering river systems in the Middle Palaeozoic was primarily an effect of environmental and tectonic conditions that prevailed during this period. These conditions induced a worldwide increase in the proportion of meandering rivers, which in turn helped favour the appropriate environment for land-plant colonization of the continents. We propose that land plants opportunistically took advantage of an appropriate global environment, which enabled them to thrive in continental environments. Fluvial environments characterized by single-channel systems and stable floodplains facilitated the greening of the land.